THE IMPACT OF NON-FORMAL ENGLISH COURSE ININCREASE THE GRAMMATICAL SKILLS OF JUNIOR HIGH SCHOOL STUDENTS - Sukmojati, Edi; Assapari, M. Mugni; Haris, Pauzan (Jurnal Ilmiah Spectral, 2023)
Non-formal English course institutions can establish a learning environment that emphasizes not only students' affective side, but also their cognitive and psychomotor components. Therefore, this study was aimed to find out The Impact of Non-Formal English Course on The Grammatical Skills.  This research uses a qualitative approach, such as a descriptive case study with observation and interviews. In addition, the data analysis used is data reduction, data display, and conclusions drawing. The findings reveal that non-formal English courses have a very good influence on students' foreign language skills. Besides having an impact on their formal school grades, these non-formal courses are also very useful in students' daily lives. In addition, students also really like the teaching methods in non-formal courses that are simple and easy to understand. Therefore, we need to know that the material obtained from informal schools is not enough to develop students' skills. Students need more intensive teaching and additional material to get satisfactory results, such as attending non-formal courses and so on.